Gambaran Pengelolaan Linen di Unit Laundry Rumah Sakit Islam Ibnu Sina Bukittinggi Tahun 2024 - Mairina Febriyanti; Zulfa, Zulfa; Abdi Setia Putra (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Health needs to be supported by non-medical services, one of which is the laundry installation. In this hospital laundry unit, it was found that linen management was still not in accordance with applicable procedures. Based on an initial survey, a problem was found, namely 561 linen declared missing in November 2022, but it turned out that in December 2022 the linen was in the room after monitoring. So this study aims to determine the description of linen management in the laundry unit. This study uses a qualitative approach with interview and observation methods with 10 informants to obtain research results. The results of this study in the human resources section of linen management training, facilities and infrastructure still do not meet the standards. In the procedure of the linen distribution stage, it was found that the recording of clean linen out was not completely filled in. For policies in the laundry unit already exist. Based on the results above, it can be concluded that linen management, namely the flow/process of linen management in the laundry unit, is not in accordance with existing standards. Suggestions for laundry officers to better comply with the SPO for linen management so that there is no recurrence of errors in recording which results in the amount of linen needed in the hospital.